Preeclampsia and academic performance in children: A nationwide study from Iceland - Sverrisson, Fridgeir A.; Bateman, Brian T.; Aspelund, Thor; Skulason, Sigurgrimur; Zoega, Helga (PloS one, 2018)
Hypertensive disorders complicate up to 10% of pregnancies. Evidence suggests a potential association between maternal hypertensive disorders during pregnancy, particularly preeclampsia, and adverse neurodevelopment in the offspring, but existing studies are subject to limitations. We aimed to assess whether in-utero exposure to preeclampsia/eclampsia negatively impacts academic performance at ages 9, 12 and 15 years. Using individually linked, nationwide data from the Icelandic registries we followed all children born in 1989-2004 (N = 68,580), from birth until the end of 2014, thereof 63,014 (91.9%) took at least one standardized test. Using a stepwise, mixed-effects approach, we modelled the hypothesized relationship while adjusting for maternal, perinatal and childhood variables of interest. We compared test scores, measured on a normalized scale ranging from 0-60 with a mean of 30 and a standard deviation of 10, in the 4th, 7th, and 10th grades, between children exposed to preeclampsia or eclampsia in-utero versus children from normotensive pregnancies in the population. Children exposed to preeclampsia/eclampsia scored lower than those unexposed in mathematics across all grade levels, corresponding to a difference of 0.44 points (95% CI: 0.00, 0.89), 0.59 points (95% CI: 0.13, 1.06) and 0.59 points (95% CI: 0.08, 1.10), respectively. No differences were observed in the language arts. Our findings suggest a minimal effect of maternal preeclampsia/eclampsia on children's academic performance at ages 9, 12 and 15 years. The differences observed in mathematic scores between exposed and unexposed children were minimal, less than one tenth of a standard deviation per measurement occasion.